The categorisation of swimming start performance with reference to force generation on the main block and footrest components of the Omega OSB11 start blocks - Slawson, S. E.; Conway, P. P.; Cossor, J.; Chakravorti, N.; West, A. A. (Journal of Sports Sciences, 2013)
Work presented in this paper provides a methodology for categorising swimming start performance based on peak force production on the main block and footrest components of the Omega OSB11 starting block. A total of 46 elite British swimmers were tested, producing over 1000 start trials. Overwater cameras were synchronised to a specifically designed start block that allowed the measurement of force production via two sets of four, tri-axis, force transducers; one set in the main block and one in the footrest. Data were then analysed, segregating trials for gender. Each start was categorised, with respect to the peak force production in horizontal and vertical components, into one of nine categories. Three performance indicators, i.e. block time, take-off velocity and distance of entry, were used to assess whether differences in performance could be correlated with these categories. Results from these data suggest that swimmers generating higher than average peak forces were more likely to produce a better overall start performance than those who produced forces lower than the average, for this population of athletes.